DEVELOPMENT OF ‘RUSSET’ SYMPTOMS ON UNDERGROUND PARTS OF POTATO PLANT - Sharma, Jyotsana; Arora, R K (Potato Journal, 2013)
‘Russet’ on potato tubers has emerged as a major problem in quality seed potato production in north-western plains of India. Most potato varieties are susceptible and exhibit a very high disease incidence. Disease etiology is not yet clear. A detailed study carried out on the development of ‘russet’ symptoms on potato plant from planting of the crop till the harvest revealed that the ‘russet’ symptoms also appear on other underground parts of potato plant. The symptoms start appearing a week after planting of the crop and continue through out the growth of the crop. Development of symptoms on other underground parts in addition to tuber differentiate this malady from common scab and is perhaps close to the netted scab caused by the Streptomyces spp.